Fundamentals-Based Estimation of Default Probabilities : A Survey - Chan-Lau, Jorge (IMF Working Papers; Working Paper ;, 2006)
This survey reviews a number of different fundamentals-based models for estimating default probabilities for firms and/or industries, and illustrates them with real applications by practitioners and policy making institutions. The models are especially useful when the firms analyzed do not have publicly traded securities or secondary market prices are unreliable because of low liquidity.